2021
DOI: 10.1002/tox.23117
|View full text |Cite
|
Sign up to set email alerts
|

Key proteins of proteome underlying sperm malformation of rats exposed to low fenvalerate doses are highly related to P53

Abstract: Fenvalerate (Fen) is an endocrine disruptor, capable of interfering with the activity of estrogen and androgen. Our objective was to explore the molecular mechanisms of Fen on sperm in vivo. Adult male Sprague-Dawley rats were orally exposed to 0, 0.00625, 0.125, 2.5, 30 mg/kg/day Fen for 8 weeks. Sperm morphology, differential proteomics of sperm and testes, bioinformatic analysis, western blotting (WB), and RT-PCR were used to explore the mechanism of Fen on sperm. Data showed that low Fen doses significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Spermatogenesis, the primary testicular function, is a complex morphological change of germ cell differentiation that involves self-renewal and differentiation of spermatogonia, meiosis of spermatocytes and spermiogenesis ( Huang et al, 2021 ). Alteration of any stage of spermiogenesis will damage sperm quality and ultimately impact male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis, the primary testicular function, is a complex morphological change of germ cell differentiation that involves self-renewal and differentiation of spermatogonia, meiosis of spermatocytes and spermiogenesis ( Huang et al, 2021 ). Alteration of any stage of spermiogenesis will damage sperm quality and ultimately impact male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that bifenthrin causes reduction in pregnancy potential and defects in fetal growth and development (Curtis et al, 2021; Park et al, 2021). Malformation of male gamates, DNA damage and epimutations in sperm and reproductive toxicity were evident in animal models that were exposed to fenvalerate, cypermethrin, permethrin, deltamethrin and fenpropathrin, respectively (Abu Zeid et al, 2021; Ha et al, 2021; Hozyen et al, 2020; Huang et al, 2021; Thorson et al, 2020). In most of the studies on pyrethroid toxicity, the effects were reported using a single compound.…”
Section: Introductionmentioning
confidence: 99%
“…The nephro‐, hepato‐, and reproductive toxicity have been reported; besides the effects on general biochemical parameters of the blood. Bifenthrin induced toxicity in the liver and kidney of mice, [ 6 ] cypermethrin induced hepatotoxicity that involved ROS mediated crosstalk between Nrf2/Keap1 and NF‐κB/iκB‐α, [ 7 ] reduction in red and white blood cell counts and increased IL‐1b production in the liver of mice exposed to sub lethal dose of λ‐cyhalothrin, [ 8 ] induction of hyperthyroidism by cypermethirn via the PI3K/Akt‐FOXA1 cascade, [ 9 ] perturbations in the biochemical parameters of lung, liver, brain, heart and testis of rats by deltamethrin, [ 10 ] permethrin induced hepatotoxicity modulated by oxidative stress and mitochondrial dysfunction, [ 11 ] genotoxicity of fenpropathrin, [ 12 ] multi organ toxicity of pyrethroid based formulations, [ 13 ] liver fibrosis in quails by activation of TGF‐beta1/Smad pathway by Han et al, [ 14 ] nephrotoxicity of fenpropathrin in rats, [ 15 ] nephrotoxicity of rabbits by Anwar et al, [ 16 ] alterations in the sperm proteome of fenvalerate treated rats, [ 17 ] permethrin induced DNA methylation epimutation markers in sperm of rats, [ 18 ] male reproductive toxicity of deltamethrin, [ 19 ] impairment of Leydig and Sertoli cell function and reproductive toxicity of bifenthrin, [ 20,21 ] and loss of male reproductive function due to cypermethrin [ 22 ] are some of the studies published in the last one and half years.…”
Section: Introductionmentioning
confidence: 99%